Drug term trends in American hip-hop lyrics. Issue 3 (21st September 2015) - Inkster, Becky; Sule, Akeem
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Many young people around the world embrace hip-hop music and culture. Since the genre's conception in the 1970s, hip-hop music and lyrics have made regular references to drugs. Understanding the relevance of these documented trends is important, especially as adolescence is a period of high risk for substance misuse. The purpose of this paper is to explore how and possibly why different lyrical trends in hip-hop music have emerged, risen and fallen out of popularity by examining word usage frequency of drug terminology in hip-hop lyrics spanning several decades of this genre. Design/methodology/approach – Electronic searches were completed using an open source database known as Rap Genius Rap Stats, which contains verified annotations and text. Word frequency was plotted against time using data available from 1988 to 2015. Word frequency was defined as a percentage of the number of hip-hop songs containing a specific drug-term (per year) based on the number of hip-hop songs recorded/produced (that year). Standardized "medical/pharmaceutical" terminologies and common "street" terminologies were plotted independently for time series visualization. Drug terms were represented using the highest frequency search term. Generic "street" terms with multiple meanings were excluded. Findings – As might be predicted, the usage of "street" terms in hip-hop lyrics was more frequently observed than the usage of "medical/pharmaceutical" terms. An exception was the term "crack", which was included in both plots as this word could be referenced as a "street" term and as a "medical/pharmaceutical" term. The authors observed larger fluctuations in "street" term usage across time relative to only slight fluctuations of "medical/pharmaceutical" term usage across time. Originality/value – In this study, the authors illustrate several drug terminology trends in hip-hop lyrics. The authors discuss some of the socio-political, socio-demographic and geographical implications that may have influenced these trends, such as the rise of the "street" term molly that emerged when molly advocating hip-hop artists became increasingly popular and a more suburban demographic transpired. This preliminary work may help to enhance two-way youth-oriented communication between health care professionals and service users, possibly improving the translation of drug-related medical messages. The preliminary work may also inform future research to consider whether such lyrical trends precede or follow changes in population substance use.